Posted in Հանրահաշիվ 7

139-141

ա)xa+xb+ya+yb

բ)a2+ab-ba-b2=a2-b2

գ)mn-3m-2n+6

դ)3x-3y-ax-ab

ե)2a-2ab-3+3b

զ)ab+3a-3b-b2

է)7×2+14xy-4y-2x

ը)a2+ab+a+b

թ)2×2+4xy+3xy+6y2

ժ)2xa-2x-a+1

ա)ab-a-1+b

բ)a+b+3a2+3ab

գ)2xa-2xb-b+a

դ)3+a+3a+a2=3+4a+a2

ե)m-2n-2xn+mx

զ)a-b-xb+ax

Posted in Հանրահաշիվ 7

128-131

128.-ա)(-a-b)(a+b)=-a2-ab-ba-b2=-a2-2ab-b2

բ)(-x+y)(x+y)=-x2-xy+yx+y2=-x2+y2

գ)(-x+y)(x-y)=-x2+xy+yx-y2=-x2+2xy-y2

դ)(-2m+n)(n-3m)=-2mn+6m2+n2-3mn=-5mn+6m2+n2

ե)(-5a+2b)(3b+2a)=-15ab-10a2+6b2+4ab=-11ab-10a2+6b2

զ)(-7x-56y)(y-3x)=-7xy+21×2-56y2+168xy=+161xy+21×2-56y2

ա)a3-2a2b+4b2a+2ba2-4b2a+8b3=a3+8b3

բ)a2+ab-ac-ba-b2+bc+ac+bc-c2=a2-ba-b2+2bc-c2

գ)(a2-2ba+2ab-4b2)(a2+4b2)=2a4+4a2b2-2a3b-8b3a+2a3b+8ab3-4b2a2-16b4=2a4-16b4

Posted in Հանրահաշիվ 7

Նոյեմբեր 9

1)x2-3x+2x-6=x2-x-6

2)10x+20x+2x+4=32x+4

3)12b-3b2+8-2b

4)8y-6y-20y+15=-18y+15

5)6a2-9a+8a-12=6a2-a-12

6)35z-14z-15z+6=+6z+6

7)2-6x-4x+12×2=2-10x+12×2

8)15x+3-10×2-2x=13x+3-10×2

9)12b2+16bc-cb-20c2=12b2+15bc-20c2

10)6×2-4xy-15xy+10y2=6×2-19xy+10y2

11)12a4-16a2b2+15a2b2-20b4=12a4-a2b2-20b4

12)+7a6-14a3b3+8b3a3-16b6=+7a6-6a3b3-16b6

13)20z2-4z4+5-z2=19z2-4z4+5

14)6-12y3-10y3+20y6=6-22y3+20y6

15)8×5-10×6+4×4-5×5=3×5-10×6+4×4

16)6×3-3×2+9x-8×2+4x-12=6×3-11×2+13x-12

17)4y4+12y3+2y3+6y2-y-3=4y4+14y3+6y2-y-3

18)12×3-20x2y-3x2y+5xy2=12×3-23x2y+5xy2

19)a3-3a2+9a+3a2-9a+27=a3+27

20)10z4-5z6-6z2+3z4-8+4z2=+13z4-5z6-2z2-8

21)18×3+24×2+10x-27×2-36x-15=18×3-3×2-26x-15

22)a4+a3-a3-a2+a2+a-a-1=a4-1

23)x4+x3y+x2y2+xy3-yx3-x2y2-xy3

Posted in Հանրահաշիվ 7

125-126

ա)a2+2a+1

բ)x2+2x+2

գ)5y+6+y2

դ)a2+2ab+b2

ե)1-x2

զ)5a-a2-b

է)x2-y2

ը)a2-2ab+b2

թ)2a2+5ab+2b2

ժ)9×2+12xy+4y2

ա)10mn+20m2+14n2+28mn=38mn+20m2+14n2

բ)36a2+60ab+3ab+5b2=36a2+62ab+5b2

գ)4×2+6xy-6xy-9y2=4×2-9y2

դ)15mn-25m2-6n2+10mn=25mn-25m2-6n2

ե)-2a2+3ab-2ab+3b2=-2a2+ab+3b2

զ)+35×2-49xy+20xy-28y2=+35×2-29xy-28y2

է)a4+a2b2+b2a2+b4=a4+2a2b2+b4

ը)m2n3-mn3-m3+m2

թ)2x2y2+4×5-y4-2y2x3

ժ)3x2y3+xy2a3+9a2xy+3a5

Posted in Հանրահաշիվ 7

114-117

ա)3(a+b) բ)2(x-y) գ)5(a+2)

դ)7(2-y) ե)6(2x+y) զ)3(a-3b)

է)5(x+1) ը)4(1-a) թ)3(4a-1)

ժ)18(1+2x) ի)6(a+c) լ)a(x-y)

խ)2a(b-3) ծ)2x(3+4y) կ)3a(4bx+5)

ա)a2(1-a+a2) բ)xy2(x2y2-x+y)

գ)a(a2+4b2) դ)5x2y(-xy-1)

ե)x(x2+x-1) զ)2ab(a2-3b3+2ab2)

է)2b(-a2+2ab-2b2) ը)2x(8+4x-2×2+x3)